Questão prejudicial e limite objetivo da coisa julgada no projeto do novo código de processo civil - Simeira, Tiago Vilhena (2014)
The present paper aims to make some comments about the proposed amendment in the Civil Process Code, which foresees magnification of the limit objective of res judicata to achieve as well, the harmful issues incidentally decided. We defined the harmful issue as a necessary step to the conclusion, that predetermines and imposes to the judge the meaning and content of the impaired decision, influencing the content of the final decision. Furthermore, it discoursed about the conceptualization of res judicata, your limit objective at the current Process Code, which is currently restricted to the command extracted from the sentence, understood in the dispositive part, and its positive function, describing the historical evolution of the institute in our legal system to the current project proposal. The American law was analyzed, in particular the issue preclusion, which is related with our institute, commenting the comparisons and criticisms of it, besides analyzing and commenting the criticisms and praises to the project’s article that predicts the modification mentioned. We concluded that the expansion of the objective limit foreseen in the project will be beneficial, because it will ensure greater legal safety, consistency, uniformity, coherence and agility, which is consistent with the ideal of economy and procedural celerity contained in the explanatory reasons of the new CPC’s project. Moreover, it tends to decrease the object of cognition of future actions, making them simpler and reduced, in addition to respecting the full utilization of procedural acts